Cost‐Effectiveness of Depression Screening for Otolaryngology–Head and Neck Surgery Residents. (8th June 2020) - Kligerman, Maxwell P.; Devine, Erin E.; Bentzley, Jessica P.; Megwalu, Uchechukwu C.
Abstract : Objectives: This study aims to determine the cost‐effectiveness of screening and treating otolaryngology–head and neck surgery residents for depression. Methods: A Markov model was built using TreeAgePro, version 2019 (TreeAge Software Inc.; Williamstown, MA) to assess the cost‐effectiveness of five potential treatment algorithms: 1) treat all residents with psychotherapy, 2) screen and treat depressed residents with psychotherapy, 3) screen and treat depressed residents with pharmacotherapy, 4) screen and treat depressed residents with combination psychotherapy/pharmacotherapy, and 5) no intervention. A Monte Carlo probabilistic sensitivity analysis (PSA), consisting of 1 thousand simulations over a cumulative 5‐year period, was performed to evaluate both base case values and a range of values for model variables. Results: Screening residents for depression and treating with combination psychotherapy/pharmacotherapy was cost‐effective and the optimal strategy at a willingness‐to‐pay threshold of $50 thousand per quality‐adjusted life year (QALY). This option demonstrated an incremental cost‐effectiveness ratio of $27, 578 per QALY for base case values. PSA confirmed these results and demonstrated that screening residents for depression and treating with either combination pharmacotherapy/psychotherapy, pharmacotherapy alone, or psychotherapy alone were cost‐effective options in 94.9% of simulations. Conclusion: Depression and burnout remain crucial issues among resident physicians. This study demonstrates that actively screening residents for depression is cost‐effective. Based on these results, residency programs may consider trialing standardized depression screening protocols. Level of Evidence: I and II. Laryngoscope, 131:502–508, 2021